Red nations the nationalities experience in and after the USSR - Smith, Jeremy (Cambridge University Press, 2013)
'Red Nations' is an accessible survey of the experience of the non-Russian USSR populace under communism. Drawing on the latest research, Jeremy Smith offers an important new contribution to the history of the dissolution of the USSR, the reconstruction of post-Soviet society, and its impact on non-Russian residents.